2020
DOI: 10.1016/j.atmosenv.2020.117429
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric nitrous acid (HONO) at a rural coastal site in North China: Seasonal variations and effects of biomass burning

Abstract: Nitrous acid (HONO) plays a significant role in atmospheric chemistry due to its contribution to hydroxyl radical (OH). However, no scientific consensus has been achieved about the daytime HONO formation mechanisms. To identify the seasonal variations of HONO chemistry and the impacts of biomass burning (BB), we performed a twophased field study in winter-spring and summer (covering a harvest season) in 2017 at a rural coastal site in North China. Though the mean HONO concentration in winter-spring (0.26 � 0.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 54 publications
2
31
0
Order By: Relevance
“…The largest P(OH)HONO reached 10.7 ppbv h -1 at 13:00 on 18 th June when HONO reached as high as 3.1 ppbv under high solar irradiance expressed as J(NO2)=6.2×10 -3 s -1 . To the best of our knowledge, such a high OH production rate from HONO photolysis, is the largest one found in rural sites, including (fertilized) agricultural sites 18,20,25,30 , forest sites 2,17 , grass sites [42][43][44] , or other rural sites 23,28 , suggesting the crucial role of soil HONO emission in the atmospheric oxidizing capacity in this region. The evident rises of O3 and H2O2 (Figure 1B and 1C) after fertilization could be attributed to the remarkable increase of P(OH)HONO that dominates the enhanced OH production, which could consequently promote the production of O3 and H2O2 through reactions (1)-( 5):…”
Section: And O3 Pollution In the Ncpmentioning
confidence: 90%
See 1 more Smart Citation
“…The largest P(OH)HONO reached 10.7 ppbv h -1 at 13:00 on 18 th June when HONO reached as high as 3.1 ppbv under high solar irradiance expressed as J(NO2)=6.2×10 -3 s -1 . To the best of our knowledge, such a high OH production rate from HONO photolysis, is the largest one found in rural sites, including (fertilized) agricultural sites 18,20,25,30 , forest sites 2,17 , grass sites [42][43][44] , or other rural sites 23,28 , suggesting the crucial role of soil HONO emission in the atmospheric oxidizing capacity in this region. The evident rises of O3 and H2O2 (Figure 1B and 1C) after fertilization could be attributed to the remarkable increase of P(OH)HONO that dominates the enhanced OH production, which could consequently promote the production of O3 and H2O2 through reactions (1)-( 5):…”
Section: And O3 Pollution In the Ncpmentioning
confidence: 90%
“…Even the non-agricultural site is ~15 km west of the sea, air mass during the measurement periods was mainly originated from the inner NCP, and no fertilization was conducted within 20 km around this site, leading to an excellent background site to verify the regional impact of agricultural fertilization. 23 At both sites, HONO was continuously measured online by the LOPAP technique (LOng Path Absorption Photometer, Model-03, QUMA GmbH, Germany) 24 . Other instruments used at the two stations are shown in Text S1 of the Supporting Information (SI).…”
Section: Sites and Instrumentationmentioning
confidence: 99%
“…Field experiments were carried out at different environments worldwide in the last few decades ( Acker et al, 2006 ; Crilley et al, 2016 ; Lee et al, 2016 ; Levy et al, 2014 ; Michoud et al, 2014 ; Spataro and Ianniello, 2014 ; Zhang et al, 2012a ). The HONO concentrations varied from a few pptv in remote areas ( Beine et al, 2001 ; Gu et al, 2020 ; Honrath et al, 2002 ; Liao et al, 2006 ; Spataro et al, 2017 ; Zhang et al, 2012a ; Zhou et al, 2001 ) to several ppbv in polluted urban environment ( Crilley et al, 2016 ; Hu et al, 2002 ; Spataro et al, 2013 ; Zhang et al, 2019e ). In China, the concentration and budget of atmospheric HONO have also been extensively studied ( Spataro et al, 2013 ), such as in Beijing ( Hendrick et al, 2014 ; Hu et al, 2002 ; Spataro et al, 2013 ; Wang et al, 2017 ; Zhang et al, 2019e ), Shanghai ( Wang et al, 2013 ; Zhang et al, 2019b ), Guangzhou ( Hu et al, 2002 ; Su et al, 2008a ), Hongkong ( Xu et al, 2015 ), Ji'nan ( Li et al, 2018 ) and Xi'an ( Huang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…ZHANG ET AL. Previous studies have reported the significant impacts of biomass burning on regional air quality over the NCP in June, the winter-wheat harvest season in northern China (Chen et al, 2017;Gu et al, 2020). In this study, we focused on the impact of biomass burning on regional O 3 concentrations.…”
Section: Sensitivity Of Regional O 3 Pollution To Coordinated Reduction Of O 3 Precursorsmentioning
confidence: 99%